فاعلية الذات و علاقتها بالتوافق الدراسي لدى تلاميذ السنة الرابعة متوسط دراسة ميدانية بمدينة الأغواط - دقشة يمينة; بيقع صليحة (My University, 2021)
The currmtStudyAimed to tryidentify the nature of the relationship and itssignicfcancebetween self-efficacy and academicadjustmentamongfourthyearstudents, average ,and also to ascertain the existence of differences in salfefficacyaccording to the gender variable amongfourth-yearstudents, and to confirmthatthere are differences in academicadjustmentaccording to the gendervariadleamongstudents of the yearfourthaverage . (100) individualswereselected as a studysampfrom a simple randomsample, and twomeasureswereused in thisstudy :the self-effectiveness cale nadiasiraj (2000) and the mamudziyadscale (1964) .for the statisticalmethodsused in the study , the (spss) system wasadopted , whicchapplied the followingstatisticalmethode : Arithmeticmean , standard deviation Pearson correlation factor , test (T) . The résults of the study are : -the existence of a statistically relevant Relationship to the interplay and school compatibility of fourt-yearstudents in the school of abd al –Qadirhaqqi al- sadiya in the city of Laghouat . -the existence of a highlevel of self-effectivenessamongstudents of the fourthyear of midddlesckool medium, in abdal-Qadirhaqqia, in the city of laghouat . -thereis a highlevel of school compatibility amongfourth-yearstudents. - there are no statisticaldifferencesbetween the sexes in the self-effectiveness of fourth-yearpupils. -there are no statisticallysignificantdifferencesbetween the sexes in the acadents of the students of the fouethyearaverage in the completion of sharkabdelQader in alsadiqiah district in the city of laghouat . seif-efficacy ,academiccompatility , fourthyearaveragestudents